Determinants of firm performance in knowledge-intensive industries: a comparative study of two emerging economies, China and Taiwan - Borah, Prasad Siba; Zhou, Lulin; Chen, Yinghua; Nisar, Numair (Advances in Social Sciences Research Journal, 2017)
In light of predictions and statistics on the increasing importance of knowledge-intensive industries in China and Taiwan, this research utilizes these two emerging economies’ business context to examine whether a firm’s performance in knowledge-intensive industries derives from industry effects or firm effects. In this study, the approach is to use multiple measures of performance, including an intellectual capital measure of performance (value added intellectual coefficient), an economic-based measure (economic value added), and an accounting based measure (return on assets). Findings suggest that firm effects greatly impact knowledge-intensive industries, in particular for value-added intellectual coefficient (VAIC). In this sense, it is proposed that organizational strategies which leverage human capital are critical to the continuous development of firms in Chinese and Taiwanese knowledge-intensive industries. Concurrently, industry effects also influence economic performance, suggesting overall that industry membership is an important indicator of a knowledge-intensive firm’s capability in value added by capital invested. This paper contributes to a scarcity of variance decomposition studies examining the sources of variation in firm performance emphasizing on knowledge-intensive industries in developing countries.